INFLUENCE OF SECRETORY FUNCTION OF SKELETAL MUSCLE ON REHABILITATION - Traverse, H. M.; Horoshko, V. I.; Hordiienko, O. V. (Rehabilitation and Recreation, 2023)
It is a well-known fact that muscles secrete proteins called myokines and participate in many processes interacting with other tissues. Current studies have shown that exercise, stimulating the skeletal muscle system in vivo, leads to the release of myokines and causes a number of effects that explain the positive effect of exercise in the treatment of diseases of the musculoskeletal system. The purpose of the work was to summarize the latest scientific developments on the influence of physical activity on the secretory function of skeletal muscles and the relationship with other organs. To achieve the goal and solve certain tasks, the following research methods were used, in particular: problem-chronological; sociological; analytical; method of terminological analysis; method of scientific extrapolation; methods of multivariate statistical analysis and forecasting – for data processing. Research methods. As well as the methods of applied system analysis, elements of probability theory, failure software design methodology were used during the work. The development of methods for simplifying the structural and functional complexity of the model was used in the research process. Recent publications have focused much attention on one such myokine, namely the recently discovered protein irisin, which is secreted into the bloodstream from skeletal muscle during exercise from the membrane-bound precursor fibronectin type III. A series of studies on irisin has provided a new look at the mechanisms of exercise to improve bone density, counteract cartilage degeneration, and support the overall environmental homeostasis of the joint. These studies add to the understanding of the role of exercise in the fight against osteoarthritis and may provide significant assistance in the development of prevention and treatment of this common disease. Recent publications have focused on the protein irisin, which is secreted into the bloodstream from skeletal muscle during exercise from the membrane-bound precursor of type III fibronectin. Irisin promotes metabolic processes such as glucose homeostasis and adipose tissue replacement. It crosses the blood-brain barrier and initiates a neuroprotective genetic program in the hippocampus, which culminates in increased expression of brain-derived neurotrophic factor. Conclusion. Most studies report that irisin concentration is closely related to health status. Studies of exercise-induced muscle factor irisin will help to better understand and explain the beneficial effects of exercise in maintaining physical health, especially in the fight against aging and age-related degenerative changes.